Stock Valuation Analysis Using The Discounted Cash Flow (DCF) Method With The Free Cash Flow To Firm (FCFF): Study Case of PT Transkon Jaya Tbk - Khanafi , Muhammad Rois; Kautsar, Achmad; Paramita , R.A. Sista (Journal of Business and Management Review, 2024)
Research Aims: This research aims to determine the fair price of TRJAshares and compare it with market prices to assess investment decisions.Design/methodology/approach: This research uses a qualitativedescriptive methodology by looking for historical data for 2018-2023,which is used as a basis for making projections for 2024-2028 using afinancial model in one company is PT Transkon Jaya Tbk. The valuationcalculation uses the discounted cash flow method with a free cash flowto-firm approach.Research Findings: The research results show that the valuation of TRJAshares using the Discounted Cash Flow method with the Free Cash Flowto Firm approach with certain assumptions is in an overvalued statewhere the intrinsic value is lower than the market price. The investmentdecisions investors can make for TRJA shares are selling if they alreadyown them or waiting until the share movement decreases to its intrinsicvalue to buy shares.Keywords: Valuation; Discounted Cash Flow; Free Cash Flow to Firm;Investment Decisions